Acceptance of accrual accounting system in public sector and its influence on job satisfaction, motivation and performance / Eveana Mosuin - Mosuin, Eveana (2016)
In 2011, the Malaysian government has announced the implementation of accrual accounting system as part of the national agenda. Following the announcement, the Accountants General Department (AGD) of Malaysia has been appointed as the agency to head and responsible for the implementation of accrual accounting system in the public sector. The shift from cash basis accounting to accrual accounting represents the fiscal management change in the Malaysian public sector. Previous studies have shown that the transition process from cash basis accounting to full adoption of accrual accounting was not easy. Countries such as Australia, New Zealand, Canada and United Kingdom took a long period of time to fully adopt the accrual accounting system. The Malaysian government however, has directed the agency to complete the full adoption of accrual accounting system within a period of only 8 years. In order to ensure the implementation success of the accrual accounting system, there is a need to examine the acceptance level of accrual accounting system among the personnel in the public sector. This study examines the acceptance level of accrual accounting system among public sector accounting personnel. Subsequently, this study examines whether the acceptance level of accrual accounting system among the public sector accounting personnel influence their motivation, job satisfaction and job performance. This study found that the public sector accounting personnel are ready for accrual accounting due to the high rate of acceptance level among them. This study also shows that the acceptance of accrual accounting system among the public sector accounting personnel significantly influences their motivation, job satisfaction and job performance. Further analyses show that employees' motivation has significant influence on job satisfaction and job performance. The results in this study indicates that acceptance of a technology leads to positive attitude among the public sector accounting personnel and this consequently influence their motivation, job satisfaction and job performance. Ultimately, accrual accounting implementation in the public sector becomes successful.